Post Enron corporate governance Business risk as a new approach to auditing - AISSAOUI , Nasreddine (Dirassat Journal Economic Issue, 2016)
Our objective through this paper is to highlight the audit strategy as a primordial tool, in order to achieve lasting corporate governance, especially after the scandals (Enron, Worldcom, Parmalat…) that shook the world of business in the early 21st century. A new audit strategy called "business risk" was developed by American audit firms at the beginning of this century to try to thwart financial scandals. The specificity of this new audit approach is not limited to the evaluation of the sincerity of the summary statements, it allows the company to be up to date in terms of advancements save in the field of business management, the characteristics of the company and its internal and external environment, as well as the almost permanent development of the obligations and rights of audit firms, etc